Transparency of Selected Materials for Infrared Electromagnetic Radiation Band Emitted From Human Body: Practical Test - F. Abdulkareem, Ali; Q. Hashim, Auns; J. Mohammed, Tariq (Al-Nahrain Journal of Science, 2025)
Infrared (IR) thermography has recently become an important tool for medical diagnoses. IR thermographic images are acquired directly from a targeted area of the human body. There are some limitations in protecting IR detectors from germ contamination through thermography which is vital to avoid contamination to from affected person to other healthy person. Other limitation is in weight-bearing thermal images. Both of these limitations require finding some material to cover IR detector or to localized between the IR detector and the detecting area, should be transparent to low-power IR emitted by human to avoid losing thermal information. This work aims to test some infrared (IR) transparent materials to find their transparency for low power IR electromagnetic radiations that are emitted from the human body in the range of 8–14 nm for the purpose of medical applications. An IR detector from Sensor Technology, model (iHA417W) with a detecting range of 8–14 microns has been used in this study by localizing several materials between IR source (human body source, and after that gas lighter flame source) and the IR detector to find the material transparency for IR emitted from the body by comparing IR temperature measurements before and after localizing these materials. The results show that among all the tested materials, only graphene (1-layer thickness of 35μm) can transmit IR emitted from the human body at a percentage of 0.67 of the emitted radiation compared to 0.13 of the IR emitted from gas lighter flame. These results conclude that graphene could be used as a cover to protect IR detectors from contamination, but it is not applicable for weight-bearing IR thermography applications because it can’t bear the weight of the body without tearing.